USULAN MODEL EVALUASI KESUKSESAN IMPLEMENTASI SISTEM INFORMASI SALES FORCE AUTOMATION MENGGUNAKAN MODEL KESUKSESAN GABLE (IS-IMPACT) - Tri Warsono Putro (Phasti: Jurnal Teknik Informatika Politeknik Hasnur, 2018)
This research discuss about how to adopt IS-Impact model by Gable, as an instrument for measuring an information system success at PT.Prudential Indonesia specially Prufuture team agency office. This reasearh aimed to propose a model which been used to evaluate information system success SalesForce Automation (SFA) that it has been used at Prufuture team office. This research focus on the identification survey in the phase of conceptual model and specification survey to validate the model by adopted the IS-Impact research methodology by Gable et al (2003 and 2008). The data collection has done by spreading an open-ended question, related to the Identification Survey step. In this survey, there were 28 respondents with 158 citations. The data were clasified based on the four dimensions of success; there are System Quality, Information Quality, Impact Individual and Organizational Impact. Based on the analysis process, we know that there were 36 of 37 indicators of IS-Impact model which felt by user at Prufuture team agency office of PT.Prudential Indonesia. Results of this analysis is identifiying a new indicator in that it can create a proposal model which become the measurement instrument in System Quality dimension, that is security. So that it creates a proposed model with 38 indicators. Keywords: Information system Impact, IS-Impact model, the success of information system, sales force automation.